Investigating Motivational Factors among EFL Students in Learning English at Kampung Inggris Jogja - Mujahidin; Margana (Britain International for Academic Research (BIAR) Publisher, 2024)
The study investigates the factors influencing English as a Foreign Language (EFL) students' motivation at Kampung Inggris Jogja, a non-formal education center. Using a qualitative phenomenological approach, data were collected through in-depth interviews with eight intermediate-level students. The analysis revealed that both intrinsic factors (interest, needs, hobbies, goals) and extrinsic factors (teachers, parents, environment) significantly affect students' motivation. The findings indicate that students are highly motivated, with a slight dominance of intrinsic motivation. The study concludes that both intrinsic and extrinsic factors are crucial in EFL learning at Kampung Inggris Jogja.